Flood vulnerability and adaptation assessment in Padang Terap district, Kedah , Malaysia - Said, Mohd Zulhafiz; Abdul Gapor, Salfarina; Hamat, Zahri (Malaysian Institute of Planners, 2024)
Padang Terap, Kedah in Malaysia experienced frequent floods, incurring financial losses to the flood victims and the government for flood mitigation. For an effective mitigation strategy, there is a need for a reliable database on the vulnerability and adaptation levels of flood victims. Therefore, this study is important to provide the data. The objectives of this paper are to analyse the factors that cause flood vulnerability and to determine and assess the existing adaptation to flood in Padang Terap. The research utilised a quantitative approach, through a household survey of 680 respondents. The data were analysed using descriptive and crosstabulation tests. The findings show that topography, distance between houses and rivers, and flood relief centres affect the vulnerability of the flood victims. The vulnerability to flood is higher than the adaptation level, implying that the Padang Terap flood victims are still not adapting to flood and prone to losses incurred related to flood.